Nurses' perception, knowledge, and use of neonatal pain assessment - Martina Carlsen Misic; Randi Dovland Andersen; Sofia Strand; Mats Eriksson; Emma Olsson (Wiley, 2021)
Abstract Preterm and sick newborn infants undergo several painful procedures during their hospital stay, potentially leading to short‐ and long‐term negative consequences. Pain assessment should be performed regularly to provide optimal pain management. Nurses' knowledge of and attitude toward neonatal pain assessment affect how pain is assessed and managed in the clinical situation. The aim of this study was to explore Swedish nurses' perception, knowledge, and use of neonatal pain assessment. This descriptive, cross‐sectional questionnaire study was conducted across all Swedish neonatal units (n = 38). Respondents were chosen through convenience sampling by the head nurses at each unit. Ten nurses from each unit were asked to complete the survey, which contained both closed and open questions. A majority of the units (30/38; 79%) participated and 232 surveys were returned, a response rate of 61%. Of the nurses, 91% thought that neonatal pain assessment was important. Many nurses mentioned various difficulties with pain assessment and concerns that the scales used might not assess pain correctly. About half of the nurses considered themselves to have enough knowledge of neonatal pain assessment. Those who reported having enough knowledge of pain assessment viewed the pain scales used at their units more positively. Of the nurses, 74% reported using a pain assessment scale several times per work shift. Pain management guidelines were available according to 75% of nurses, but only 53% reported that the guidelines were followed. Although nurses in general expressed a positive attitude toward pain assessment scales, this was not necessarily evident in their clinical practice. Lack of knowledge, available or accessible guidelines, or concerns regarding the validity of available pain scales seemed to limit their use.